2009
DOI: 10.1093/jpepsy/jsp060
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Parent Training as an Adjunct to Routine Care in Children with Attention-Deficit/Hyperactivity Disorder: Moderators of Treatment Response

Abstract: Adjunctive BPT is most useful when mothers have high parenting self-efficacy and in children with no or single-type comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 23 publications
6
64
0
3
Order By: Relevance
“…The findings in Table 2 indicate that effects of time and Time ϫ Treatment Group were statistically significant, which is in line with our earlier findings ( Van den Hoofdakker et al, 2007, 2010. In addition, a statistically significant interaction effect between time, treatment group, and DAT1 genotype was present.…”
Section: Resultssupporting
confidence: 90%
“…The findings in Table 2 indicate that effects of time and Time ϫ Treatment Group were statistically significant, which is in line with our earlier findings ( Van den Hoofdakker et al, 2007, 2010. In addition, a statistically significant interaction effect between time, treatment group, and DAT1 genotype was present.…”
Section: Resultssupporting
confidence: 90%
“…Johnston et al (2010) report that mothers with higher parenting efficacy view behavioural strategies as more likely to being effective, which predicts positive treatment experience. In the same line are the results of Van den Hoofdakker et al (2010) who have reported that behavioural parent training is most useful when mothers have high parenting self-efficacy and when children have no or just one single type of co-morbidity. Thus, the management of the child's behaviour and parental intervention could be useful in the promotion of more positive parental functioning.…”
Section: Discussionmentioning
confidence: 78%
“…41 Randomized controlled trials in children with ADHD have shown good effi cacy with a number of behavioral interventions and parent-training programs, including those that target organizational and timemanagement skills, externalizing behaviors (eg, aggression and defiance), and social skills. 7,8,[42][43][44][45] Additionally, the effectiveness of behavioral treatment, either alone or in combination with pharmacotherapy, was evaluated in the Multimodal Treatment Study of Children with ADHD (MTA). 46 While rates of successful treatment response were lower with behavioral treatment alone than with pharmacotherapy alone, almost three-fourths of the behavioral treatment group were treated for 14 months without acute exacerbations or other situations requiring the administration of pharmacotherapy.…”
Section: Case 1: John Ymentioning
confidence: 99%